The Visual dictionary of military uniforms. - Dorling Kindersley, Inc. (New York : Kindersley/Houghton Mifflin, 1992)
Labeled illustrations with explanatory text show the parts of various military uniforms that have been used from ancient Roman times to the twentieth century.
Includes index.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
7.5
5-8
Keywords: Military uniforms -- Pictorial works -- Juvenile literature; Military uniforms -- Terminology -- Juvenile literature; Picture dictionaries, English -- Juvenile literature; Military uniforms; Military uniforms